O mito de Enéias e a Elegia de Propércio - Oliva Neto, João Angelo (Classica - Revista Brasileira de Estudos Clássicos, 1989)
This essay intends to stablish the myth of Aeneas as the reason of some dificulty that the elegiacs found to touch their very theme-love, as seen in the work of Sextus Propertius. Considering that his leaving Dido behind signifies the overcoming of Love’s vulnerability in the Roman civilization, it’s shown that once for all the higher designs of Jupiter are preferable and more important even when Love may come from a goddess, from so near a person to Aeneas as his mother Venus. Then it's shown that there’s a necessary link between the elegiac mode and peace as a atheme and as a manner of opposing to the epic war-like subjects. Naive as it may be, Love belongs to the divine sphere in which everything alive is preserved; this divinity, that the Romans received from the Greeks. Is what is most cared to by the elegiacs, in the person and figure of Venus, mother of Julia race.